2022
DOI: 10.33225/jbse/22.21.1191
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Factors That Affect Undergraduate Students' Motivation to Learn Chemistry and Physics

Abstract: The pivotal role of motivation in fostering science learning has long been recognized and it is a field of active research worldwide. This research aimed at examining the effect of three different factors (used as independent variables) on shaping the motivation of undergraduate students for chemistry and physics learning via multiple regression analysis. Motivation (dependent variable) was measured via the use of the chemistry and physics-specific versions of Science Motivation Questionnaire II (SMQ II). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 25 publications
2
4
1
Order By: Relevance
“…Meanwhile, the predictor that always appears in the regression equation is gender difference (female). This finding contrasts the results of a study by Salta and Koulougliotis (2022) which said that gender was not included in the regression equation that was formed. It can be said that gender difference in this study is the predictor that has the highest predictive power of students' learning motivation to learn chemistry (with a value of b, 0.876 < b < 1.904).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Meanwhile, the predictor that always appears in the regression equation is gender difference (female). This finding contrasts the results of a study by Salta and Koulougliotis (2022) which said that gender was not included in the regression equation that was formed. It can be said that gender difference in this study is the predictor that has the highest predictive power of students' learning motivation to learn chemistry (with a value of b, 0.876 < b < 1.904).…”
Section: Discussioncontrasting
confidence: 99%
“…The low coefficient value (-.013 < r < .131) implies that class differences did not significantly influence students' motivation to learn chemistry. In previous studies, it has been revealed that academic majors have low and moderate correlations (Salta & Koulougliotis, 2022). In line with this study, at the upper-secondary school level, class differences also did not significantly affect motivation to learn chemistry.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The methodology employed in this study was that of a quantitative cross-sectional and correlational analysis. Quantitative or measurable data on multiple variables are collected and analyzed in a cross-sectional study to uncover correlations or other patterns (Salta & Koulougliotis, 2022). Additionally, since the aim of the current study was to provide an explanation for the correlation between variables, it is more accurately labelled as explanatory research (Creswell, 2002).…”
Section: Methodsmentioning
confidence: 99%